1978
DOI: 10.1128/jb.135.3.993-997.1978
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes producing 4-thiouridine in Escherichia coli tRNA: approximate chromosomal locations of the genes and enzyme activities in a 4-thiouridine-deficient mutant

Abstract: A previously described mutant of Escherichia coli which lacks 4-thiouridine in its tRNA was here shown to be deficient in factor A, one of the two proteins responsible for this thiolation of uridine. Addition of exogenous factor A restored the thiolating ability of extracts prepared from the mutant. The activities of the two thiolation proteins were governed by genes at two widely separated positions on the chromosome, as determined with F-prime merodiploids. The site governing factor A activity lay roughly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 13 publications
(6 reference statements)
3
15
0
Order By: Relevance
“…Abbreviations refer to the nucleotide 3'-phosphate: ms2i6A, 2-methylthio-6-isopentenyl adenylic acid ; s4U, 4-thiouridylic acid; s2C, 2-thiocytidylic acid : mamss2U, 5-methylaminomcthyl-2-thiouridylic acid minor absorption band (iVmax = 337 nm) due to s4U [24] ; (b) illumination followed by NaBH4 reduction failed to produce the 385-nm absorption band and the fluorescence = 450 nm) characteristic of the reduced 8-13 link; (c) chromatographic analysis of the RNAse Tz digests of the tRNAs of the wild type (Fig. 1) labeled with radioactive sulfur indicates that s4U accounts for 60"/, of the total sulfur content of the tRNA, in agreement with the report of Lipsett [31]. In PM2 cells the level of s4U decreases to less than 0.2%, whereas thar of other thiolated bases is unaffected.…”
Section: Numbersupporting
confidence: 81%
See 1 more Smart Citation
“…Abbreviations refer to the nucleotide 3'-phosphate: ms2i6A, 2-methylthio-6-isopentenyl adenylic acid ; s4U, 4-thiouridylic acid; s2C, 2-thiocytidylic acid : mamss2U, 5-methylaminomcthyl-2-thiouridylic acid minor absorption band (iVmax = 337 nm) due to s4U [24] ; (b) illumination followed by NaBH4 reduction failed to produce the 385-nm absorption band and the fluorescence = 450 nm) characteristic of the reduced 8-13 link; (c) chromatographic analysis of the RNAse Tz digests of the tRNAs of the wild type (Fig. 1) labeled with radioactive sulfur indicates that s4U accounts for 60"/, of the total sulfur content of the tRNA, in agreement with the report of Lipsett [31]. In PM2 cells the level of s4U decreases to less than 0.2%, whereas thar of other thiolated bases is unaffected.…”
Section: Numbersupporting
confidence: 81%
“…The nuv gene is either the structural gene for the thiolase itself or a regulatory gene. Recently Lipsett [31] has shown that in the Eschericlzia coli B/r s4Udeficient strain, isolated by Ramabhadran et al [18], the activity of the thiolation factor A was greatly depressed in contrast to the activity of factor C the other factor required for thiolation in vitro [34]. Furthermore, the site governing factor A activity was approximately located, by the gene clonage technique, in a region of the chromosome which includes the nuv locus.…”
Section: Selection Proceduresmentioning
confidence: 99%
“…Details of these findings are given in the reviews cited above Several recent papers deal with the chromophore for growth delay. Lipsett [31] measured chemically the "Srd in a "Srd-mutant of E. coli B/r (RJ). isolated by Ramabhadran rr ul.…”
mentioning
confidence: 99%
“…An E. coli K-I2 gene (nut), controlling the production of 4-thiouridine in tRNA. was located at 9.3 0.2 min on the chromosome map by Thomas and Favre [@I. Escherichia coli B/r NC32 RJ [45] was shown by Lipsett [31] to be deficient in factor A. m e of the two proteins responsible for 4-thiolation of uridine. The site that governs factor A lies roughly in the region of nut.…”
mentioning
confidence: 99%
“…This conformational change reduces the acylation capacity of several species of tRNA and ultimately results in an inhibition of protein synthesis (23). One of the two thiolation factors responsible for the modification of uracil residues is the product of the nuvA locus (24). Strains lacking this thiolation activity are not growth inhibited by near-UV irradiation, thus allowing the study of DNA repair factors (both constitutive and inducible) required for the repair of near-UV-mediated DNA damage.…”
Section: Introductionmentioning
confidence: 99%